Profiles of Wnt pathway gene expression during tooth morphogenesis - Raju, Resmi; Piña, Jeremie Oliver; Roth, Daniela M.; Chattaraj, Parna; Kidwai, Fahad K.; Faucz, Fabio R.; Iben, James; Fridell, Gus; Dale, Ryan K.; D’Souza, Rena N. (Frontiers in Physiology, 2024)
Mouse and human genetic studies indicate key roles of the Wnt10a ligand in odontogenesis. Previous studies have identified effectors and regulators of the Wnt signaling pathway actively expressed during key stages of tooth morphogenesis. However, limitations in multiplexing and spatial resolution hindered a more comprehensive analysis of these signaling molecules. Here, profiling of transcriptomes using fluorescent multiplex in situ hybridization and single-cell RNA-sequencing (scRNA-seq) provide robust insight into the synchronized expression patterns of Wnt10a, Dkk1, and Sost simultaneously during tooth development. First, we identified Wnt10a transcripts restricted to the epithelium at the stage of tooth bud morphogenesis, contrasting that of Sost and Dkk1 localization to the dental mesenchyme. By embryonic day 15.5 (E15.5), a marked shift of Wnt10a expression from dental epithelium to mesenchyme was noted, while Sost and Dkk1 expression remained enriched in the mesenchyme. By postnatal day 0 (P0), co-localization patterns of Wnt10a, Dkk1, and Sost were observed in both terminally differentiating and secreting odontoblasts of molars and incisors. Interestingly, Wnt10a exhibited robust expression in fully differentiated ameloblasts at the developing cusp tip of both molars and incisors, an observation not previously noted in prior studies. At P7 and 14, after the mineralization of dentin and enamel, Wnt10a expression was limited to odontoblasts. Meanwhile, Wnt modulators showed reduced or absent signals in molars. In contrast, strong signals persisted in ameloblasts (for Wnt10a) and odontoblasts (for Wnt10a, Sost, and Dkk1) towards the proximal end of incisors, near the cervical loop. Our scRNA-seq analysis used CellChat to further contextualize Wnt pathway-mediated communication between cells by examining ligand-receptor interactions among different clusters. The co-localization pattern of Wnt10a, Dkk1, and Sost in both terminally differentiating and secreting odontoblasts of molars and incisors potentially signifies the crucial ligand-modulator interaction along the gradient of cytodifferentiation starting from each cusp tip towards the apical region. These data provide cell type-specific insight into the role of Wnt ligands and mediators during epithelial-mesenchymal interactions in odontogenesis.